2018
DOI: 10.2478/macvetrev-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Different Dynamics of Sensory-Motor Development and Behavior During the Transitional Period in Puppies: Preliminary Results

Abstract: Many studies have analyzed the behavior of puppies during their socialization period, while little attention has been paid to the transitional period, when vision and hearing develop. Here, we compared the average age of sensory and motor development, and the behavior among a total of 25 puppies. Each litter was videotaped during 1-hour daily sessions on postnatal days 10-21 and coded for the following mutually exclusive behavioral categories: sleeping, suckling and moving. The moving category included side-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…The puppy's eyes were open for the first time at around two weeks of age. which is quite in line with what other investigators have reported (Pirrone et al 2018).…”
Section: Discussionsupporting
confidence: 94%
“…The puppy's eyes were open for the first time at around two weeks of age. which is quite in line with what other investigators have reported (Pirrone et al 2018).…”
Section: Discussionsupporting
confidence: 94%